Improvement of overall survival in the Collaborative Wilms Tumour Africa Project. Issue 9 (11th May 2020) - Chagaluka, George; Paintsil, Vivian; Renner, Lorna; Weijers, Janna; Chitsike, Inam; Borgstein, Eric; Kamiza, Steve; Afungchwi, Glenn M.; Kouya, Francine; Hesseling, Peter; Molyneux, Elizabeth; Israels, Trijn
Abstract: Introduction: The Collaborative Wilms Tumour (WT) Africa Project implemented an adapted WT treatment guideline in six centres in sub‐Saharan Africa. The primary objectives were to describe abandonment of treatment, death during treatment, event‐free survival (EFS) and relapse following implementation. An exploratory objective was to compare outcomes with the baseline evaluation, a historical cohort preceding implementation. Methods: The Collaborative WT Africa Project is a multi‐centre prospective clinical trial that began in 2014. Funding was distributed to all participating centres and used to cover treatment, travel and other associated costs for patients. Patient characteristics, tumour characteristics and events were described. Results: In total, 201 WT patients were included. Two‐year EFS was 49.9 ± 3.8% when abandonment of treatment was considered an event. Relapse of disease occurred in 21% (42 of 201) of all included patients and in 26% (42 of 161) of those who had a nephrectomy. Programme implementation was associated with significantly higher survival without evidence of disease at the end of treatment (52% vs 68.5%, P = .002), significantly reduced abandonment of treatment (23% vs 12%, P = .009) and fewer deaths during treatment (21% vs 13%, P = .06). Conclusion: This collaborative implementation of an adapted WT treatment guideline, using relatively simple and low‐cost interventions, was feasible. Two‐year EFS was almost 50%. In addition, a significant decrease in treatment abandonment and an increase in survival at the end of treatment were observed compared to a pre‐implementation cohort. Future work should focus on decreasing deaths during treatment and will include enhancing supportive care.